An E/e′ ratio on echocardiography predicts the existence of left atrial low-voltage areas and poor outcomes after catheter ablation for atrial fibrillation. Issue 5 (22nd June 2017) - Masuda, Masaharu; Fujita, Masashi; Iida, Osamu; Okamoto, Shin; Ishihara, Takayuki; Nanto, Kiyonori; Kanda, Takashi; Sunaga, Akihiro; Tsujimura, Takuya; Matsuda, Yasuhiro; Ohashi, Takuya; Uematsu, Masaaki
Abstract: Aims: An elevated left atrial pressure has been reported to play an important role in the development of atrial remodelling in atrial fibrillation (AF) patients. The study aimed at elucidating the association between the diastolic early transmitral flow velocity/mitral annular velocity ( E / e ′, a non-invasive surrogate of left atrial pressure) and left atrial low-voltage-area existence, and the prognostic impact of the E / e ′ on procedural outcomes in patients undergoing AF ablation. Methods and results: Total of 215 consecutive patients were divided into 3 groups based on the estimated left atrial pressure: normal ( E / e ′ < 8.0, n = 58), undetermined ( E / e ′ = 8.0–14.0, n = 114), and elevated ( E / e ′ > 14.0, n = 43). Left atrial endocardial voltage mapping was performed following pulmonary vein isolation. Patients with a high E / e ′ more frequently had low-voltage areas ( E / e ′ < 8.0, 31%, E / e ′ = 8.0–14.0, 35%; E / e ′ > 14.0, 67%; P = 0.0001). After adjusting for other correlates, a high E / e ′ was an independent predictor of low-voltage-area existence (HR = 1.11, 95% CI = 1.02–1.21, P = 0.017). During a mean follow-up period of 12 ± 6 months, recurrent atrial tachyarrhythmias occurred in 22 (10%) patients after multiple (1.4 ± 0.5) procedures. Patients with an E / e ′ > 14 had more frequent recurrent atrial tachyarrhythmias after multiple ablation procedures than those with an E / e ′ ≤ 14 (23% vs. 7%, P = 0.001). Conclusion: A high E / e ′ obtained by pre-ablation echocardiography was associated with a left atrial arrhythmogenic substrate in patients undergoing AF ablation. Furthermore, a high E / e ′ predicted poor procedural outcomes after pulmonary vein isolation.